International trade and finance : new frontiers for research : essays in honor of Peter B. Kenen - .Cohen, Benjamin J. (Cambridge University Press, 1997)
This collection of original essays offers a selection of contemporary scholarship intended to help define an agenda for future research in the field of international trade and finance. Written to honour Peter B. Kenen and to follow his work, the volume is divided into three parts: international trade theory, international monetary theory, and applied policy analysis. Trade issues addressed include the role of capital in standard trade models, welfare implications of economic integration, and the relationship between economic openness and the size of government. The monetary chapters include two related essays on the effects of exchange rates on economic activity and two essays on aspects of optimum currency area theory. Applied policy papers include two on industrial countries, two on developing countries, and one on problems of transition in the successor states of the former Soviet Union. Also included is an essay by Paul Krugman assessing Kenen's lifetime of scholarly achievements.